Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 2997 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Coccinellidae", "Country is United States of America", "Year is greater than or equal to 2014" ] } The dataset includes 2997 records from 6 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004581-160509122628363/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences